Effect of deficit irrigation on dry matter and sheep production from permanent sown pastures - Isik S; Ates, S.; Gunes A; Aktas AH; Keles G (2012)
Grassland-based systems are no longer seen exclusively as livestock production enterprises but as multiple use systems with important consequences for the global environment. They are crucial for the protection of ecosystem goods and services, for tourism and for mitigating climate change. Well-managed grasslands provide important benefits such as increased water infiltration and retention or improved nutrient cycling, associated with organic matter accumulation in the soil, as well as increased plant growth and diversity of species. Thereby grassland management is also an adaptation strategy for climate change, as it reduces the risks associated with prolonged drought periods and unreliable rains that characterise Mediterranean regions. There is an urgent need to assess the interaction between climate change and grasslands to identify appropriate options that can help farmers to manage forage resources under increasing drought conditions and market globalisation. The challenge is then to improve grassland productivity, pasture persistence and resilience under these constraints. Scientific advances in grassland management and new strategies in plant improvement may undoubtedly contribute to this aim. This publication is the outcome of the 14th Meeting of the FAO-CIHEAM Inter-regional Cooperative Research and Development Sub-Network on Mediterranean Pastures and Fodder Crops titled "New approaches for grassland research in a context of climatic and socio-economic changes" which was organised in Samsun (Turkey) from 3 to 6 October 2012, and includes the invited and selected papers presented at the Meeting. The published articles, written by authors from different countries of the different Mediterranean climate areas of the world, cover a range of topics grouped into the sessions of the Meeting: (i) Climate change and grasslands: impacts, adaptation and mitigation, (ii) Selection of pasture and forage species under climate and socio-economic changes; (iii) Role and management of permanent grasslands; (iv) Changes in Mediterranean farming systems to meet new socio-economic scenarios; and (v) Mediterranean grassland research: priorities and future challenges".